The relevance of the concept of good governance: revisiting goals, agendas and strategies - Khan, Akbar Ali (© 2015 Springer International Publishing, 2016)
This book chapter was published in the Governance in South, Southeast, and East Asia: Trends, Issues and Challenges. [© 2015 Springer International Publishing Switzerland. ] and the definite version is available at :http://dx.doi.org/10.1007/978-3-319-15218-9_7. The book chapter's website is at: http://link.springer.com/chapter/10.1007%2F978-3-319-15218-9_7